Computer simulations of cross-current sedimentation process - Kowalski, W.; Migso, R. (Видавництво Національного університету «Львівська політехніка», 2004)
Теоретично розглянуто спрощену математичну модель відкладання осаду. Дві асиметричні і паралельні пластини обмежують область процесу і визначають поперечний потік формування осаду в елементарному просторі резервуара Результати комп’ютерного моделювання поперечного потоку під час формування осаду базуються на описаній математичній моделі. The sedimentation process simplified mathematical model is being considered theoretically in the article. The two skew and parallel plates limit the process area and determine the cross-current multiflux sedimentation tank elementary space. The results of the cross-current sedimentation process computer simulations, based on the described mathematical model, are introduced too.